The X Files : Season 5 Disc 2 - Bowman, Rob, 1960-; Gillian, Anderson; William B Davis; John Neville; David Duchovny (Canada, USA Ten Thirteen Productions, 1998)
Two people from two worlds. FBI Agent Fox Mulder, a believer. FBI Agent Dana Scully, a Skeptic. Together they must solve the mysteries such as who, or what destroyed a Federal Building in Dallas, what killed 4 firemen and a child supposedly killed in the blast and more, but these mysteries were not placed by some insane terrorist, these were placed by our very own Government.
Mulder and Scully must fight the government in a conspiracy and find the truth about an alien colonization of Earth.
Chris Carter
Languages: English, French, Italian, German, Spanish, Japanese Subtitles: Dutch, English, French, Greek, Italian
Keywords: SciFi; Tv Series